2015
DOI: 10.1371/journal.pone.0136484
|View full text |Cite
|
Sign up to set email alerts
|

Musashi-2 Silencing Exerts Potent Activity against Acute Myeloid Leukemia and Enhances Chemosensitivity to Daunorubicin

Abstract: RNA-binding protein Musashi-2 (Msi2) is known to play a critical role in leukemogenesis and contributes to poor clinical prognosis in acute myeloid leukemia (AML). However, the effect of Msi2 silencing on treatment for AML still remains poorly understood. In this study, we used lentivirus-mediated RNA interference targeting Msi2 to investigate the resulting changes in cellular processes and the underlying mechanisms in AML cell lines as well as primary AML cells isolated from AML patients. We found that Msi2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 33 publications
3
33
0
Order By: Relevance
“…Nowadays, few studies report the association of MSI2 with drug resistance, and the corresponding mechanisms are poorly understood. MSI2 silencing exhibits markedly higher proliferation‐inhibiting rates and enhances daunorubicin‐induced cell apoptosis in Dami cells and primary AML cells (40). The gene expression profile in the two clusters of small‐cell lung cancer cells [poly(ADP) ribose polymerase inhibitor sensitive vs. insensitive] before and after exposure to cisplatin and veliparib revealed a panel of 5 genes that are restricted to the sensitive cell lines (including MSI2) (41).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, few studies report the association of MSI2 with drug resistance, and the corresponding mechanisms are poorly understood. MSI2 silencing exhibits markedly higher proliferation‐inhibiting rates and enhances daunorubicin‐induced cell apoptosis in Dami cells and primary AML cells (40). The gene expression profile in the two clusters of small‐cell lung cancer cells [poly(ADP) ribose polymerase inhibitor sensitive vs. insensitive] before and after exposure to cisplatin and veliparib revealed a panel of 5 genes that are restricted to the sensitive cell lines (including MSI2) (41).…”
Section: Discussionmentioning
confidence: 99%
“…As some examples, elevated expression of MSI2 induced resistance to paclitaxel in ovarian cancer cells in vitro (27). MSI2 silencing in AML cells sensitized these cells to treatment with daunorubicin, accompanied by induction of cell cycle arrest and induction of apoptosis, mediated by downregulation of BCL2 and upregulation of BAX (35). MSI1 was recently described as a regulator of response to radiation therapy in glioblastoma.…”
Section: Musashi Proteins In Tumor Responses To Chemotherapy and Radimentioning
confidence: 99%
“…As such, it mediates mRNA stability and translation of proteins involved in oncogenic pathways . Overexpression and knockdown studies indicate that MSI2 is a promising therapeutic target for cancer …”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Overexpression and knockdown studies indicate that MSI2 is a promising therapeutic target for cancer. 3,13,16,21,22 Human MSI2 is a 328 amino acid protein that contains two RNA recognition motifs (RRMs) spanning G21-K111 (RRM1) and K110-P187 (RRM2). A BLAST 23 search revealed that MSI2 (residues F I G U R E 1 Clustal multiple sequence alignment of human MSI2, human MSI1, and mouse MSI1.…”
Section: Introductionmentioning
confidence: 99%